Analisis Beban Kerja Polri Menggunakan Metode Workload Analysis dan PIECES Pada Unit Binmas Polsek Ilir Barat 1 Palembang - Micky Sefriyandi; Kiky Rizky Nova Wardani (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
The Indonesian National Police (Polri) is a state institution tasked with maintaining public safety and order, enforcing the law, and providing protection, guidance, and services to the community. The objective of this community service project is to analyze the workload of the Indonesian National Police using the Workload Analysis (WLA) method and to identify the factors that influence the effectiveness of task performance using the PIECES framework. The results of this community service project indicate that the main problem at the Community Guidance Unit (Binmas) of the Ilir Barat 1 Police Station in Palembang is not caused by low individual performance among personnel, but rather by a structural imbalance between the workload and the number of available personnel. The high volume of work is not matched by adequate human resource capacity, which has the potential to affect the effectiveness of task execution if no adjustments are made.